2013
DOI: 10.1016/j.eneco.2012.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Non-linearities in the dynamics of oil prices

Abstract: We utilize non-linear models to examine the stationarity of oil prices (Brent, Dubai, WIT and World) over the period 1973:2-2011:2. Real oil prices are calculated and expressed in the domestic currencies of seven Asian countries (Indonesia, Japan, Korea, Malaysia, the Philippines, Singapore and Thailand) and in the U.S dollar.Applying linear unit root tests with and without structural breaks shows very limited evidence of stationarity.However, applying non-linear models shows evidence of non-linearity in all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The results are not reported here for the sake of parsimony. (Nonlinearity in real oil price time series, ascertained by means of univariate LSTAR/ESTAR tests is to be found also in Kisswani and Nusair, 2013. ) 14.…”
Section: Robustness Analysis Of the Model Specificationmentioning
confidence: 82%
“…The results are not reported here for the sake of parsimony. (Nonlinearity in real oil price time series, ascertained by means of univariate LSTAR/ESTAR tests is to be found also in Kisswani and Nusair, 2013. ) 14.…”
Section: Robustness Analysis Of the Model Specificationmentioning
confidence: 82%
“…Moreover, in a nonlinear structure, the reaction of the stock prices to the positive shocks of the economy may differ from that to the negative shocks. In this section, the nonlinear short- and long-run term relationship between cryptocurrencies on gold and on the G7 and the BRICS index has been examined by empirical literature (Kisswani and Nusair, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Huang et al [31] and Hou [28] presented superior performance of non-parametric GARCH models relative to parametric GARCH models (in-sample and out-of-sample volatility forecasts). Researchers concluded that non-linear dynamical approach is more appropriate for characterizing and predicting crude oil prices than linear approach [32,33]. The parameters of forecasting models for crude oil prices have been estimated by either Least Square Method [12,23,[34][35][36][37][38], Full Information Likelihood Method [16], Kalman Filter [23,24] or under Bayesian Framework [39].…”
Section: Time Series Modelmentioning
confidence: 99%